Pengaruh Self-Regulated Learning dalam Meningkatkan Disiplin Belajar Siswa Kelas XII SMK Negeri 12 Kota Bekasi - Yusuf Maulana; Misbah Fikrianto (Guidance : Jurnal Bimbingan dan Konseling, 2021)
This study aims to determine the effect of self-regulated learning in improving student discipline at SMK Negeri 12 Kota Bekasi. The method used in this research is quantitative experiment. The population were 73 students with a research sample of 36 students who were taken with the Purpose Sampling technique. The instrument used is a self-regulated learning scale and a learning discipline scale. The analysis used is hypothesis testing with t-test. The results of the calculation using the sample T-test with a significance value of the paired sample test T-test 0.00 <0.05 and the independent sample T-test test value of 0.689> 0.05, it means that there is a significant effect on the experimental class and the hypothesis obtained it is proven that there is a significant difference in the learning discipline of the XII grade students of SMK Negeri 12 Kota Bekasi before and after the treatment.